2017
DOI: 10.12775/jcrl.2016.020
|View full text |Cite
|
Sign up to set email alerts
|

CSR as a Source of Competitive Advantage: The Case Study of Polpharma Group

Abstract: Purpose: The main purpose of this paper is to analyse the relations between CSR activities and competitive advantages. it discusses how companies undertake CSR activities and what benefits can be gained because of these activities. Methodology/approach: The paper is based on the Polpharma' s single case study. The narrative literature review was applied to build up the theoretical foundation for the empirical study. Findings: CSR activities undertaken by companies can be a source of many benefits, which may tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
3
11
0
Order By: Relevance
“…Various researchers work on the social responsibility of companies [56][57][58][59][60][61]; however, these studies misses with the roles of achieving a competitive advantage and sustainable business performance. It is found that the social responsibility of organization affects sustainable competitive advantage [62][63][64][65]. Better social responsibility achievement increases the competitive advantage of companies.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Various researchers work on the social responsibility of companies [56][57][58][59][60][61]; however, these studies misses with the roles of achieving a competitive advantage and sustainable business performance. It is found that the social responsibility of organization affects sustainable competitive advantage [62][63][64][65]. Better social responsibility achievement increases the competitive advantage of companies.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…The same results were also found in research conducted by Kang and Hustvedt (2014): CSR significantly positively affects customer trust and attitudes towards the company. Research by Cegliński and Wiśniewska (2016) and Jalilvand et al (2017) also found that CSR affects customer trust in a significantly positive manner. Referring to the findings of the research results, the following research hypothesis was built:…”
Section: Customer Trustmentioning
confidence: 89%
“…Many previous studies have concluded that CSR significantly affects customer trust (Cegliński & Wiśniewska, 2016;Choi & La, 2013;Jalilvand et al, 2017;Kang & Hustvedt, 2014;Swaen & Chumpitaz, 2008). In addition, it has been found that the relationship between customer trust and business sustainability is significant (Rousseau, et al, 1998;Singh & Sirdeshmukh, 2000;Upamannyu et al, 2015;Wu et al, 2010;Yu et al, 2018).…”
Section: Customer Loyaltymentioning
confidence: 97%
See 1 more Smart Citation
“…In the case of mentioned company there are two categories related with the CSR concept that are of fundamental importance -trust and firm's reputation. Generally, it is assumed that they are the result of socially responsible activities (Cegliński and Wiśniewska, 2016).…”
Section: Sources Of Competitive Advantagesmentioning
confidence: 99%